Short Videos on Social Media as Catalysts for English Language Learning Beyond the Classroom - Assakhi, Sanna Mohammad; Fakhrurriana, Ria (BATARA DIDI : English Language Journal, 2023)
The demand for technology supports and engaging students in their second language beyond the classroom has caused an uptrend of using technology media, especially short videos on social media. In this current investigation, a Systematic Literature Review (SLR) research approach is used in order to analyse the features, prospects, pitfalls, and approaches connected with social media, short video use in grasping English language. Altogether, the observations indicate that the students improve their language proficiency vocabulary and speaking and listening as they watch short videos on the apps like TikTok and Instagram Reels. However, there are problems in the integration of these tools such as issues concerning the content accuracy, distraction, and the inconsistency in educational content used. The paper also underscores significant responsibility of teachers in selecting and presenting quality content, as well as developing learners’ digital competencies to realise necessary learning affordances of these technologies. In overcoming these challenges, educators are in a better position to assist the students to overcome the challenges and use the short videos for learning a language. The results also present hypotheses for further research: the outcomes of the study also indicate the conditions under which the number of videos will give the best result and possible long-term effects of its using on the language achievement.